2023
DOI: 10.3389/fphys.2023.1185343
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and combined hormonal contraception: association with female students’ perception of menstrual symptoms

Abstract: Aim: The aim of this study was to examine the association between physical activity (PA) and combined hormonal contraceptive (CHC) on female students’ self perceptio of their menstrual cycle symptoms.Methods: Healthy French female students (n = 834) completed an online questionnaire to assess their PA level (Group 1: non-active; Group 2: moderate physical activity; Group 3: high physical activity; Group 4: very high physical activity), menstrual status or contraception use, self-reported diet and medication, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…In our study, the women who resorted to condoms as contraceptive methods had to resort more to sick leaves than those using hormonal methods. This is also in line with the result which indicates that the youngest women are the ones with the most menstrual symptoms, both pain and abundant bleeding; in addition, it is the contraceptive method most frequently used in this age group as well [ 14 , 20 ]. In turn, this leads them to having to resort to work absences and/or to request sick leaves more frequently.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our study, the women who resorted to condoms as contraceptive methods had to resort more to sick leaves than those using hormonal methods. This is also in line with the result which indicates that the youngest women are the ones with the most menstrual symptoms, both pain and abundant bleeding; in addition, it is the contraceptive method most frequently used in this age group as well [ 14 , 20 ]. In turn, this leads them to having to resort to work absences and/or to request sick leaves more frequently.…”
Section: Discussionsupporting
confidence: 85%
“…In this research, menstrual pain has been related to the use of contraceptive methods, noticing that the highest painful menses rates are found among those women who resort to condoms as a contraceptive method. In other studies, it has been already shown that using contraceptive methods can reduce menstrual pain and improve women’s quality of life [ 9 , 10 , 19 ], although we should also acknowledge that dysmenorrhea can be the result of several factors such as nutrition, physical exercise, stress, sleep [ 20 , 21 ] and even gynaecological problems such as endometriosis [ 7 , 11 , 22 ]. Therefore, it would be interesting to analyse it considering all these factors that have been described.…”
Section: Discussionmentioning
confidence: 99%
“…First, there was a tendency among athletes and coaches to prioritise sport training and performance above their health and well-being, with athletes ignoring pain and discomfort due to menstrual symptoms unless they were found to impact performance. 24,28,31,34,37,42,45,47 Given that complete rest and light-intensity physical activity are commonly-employed methods for coping with dysmenorrhea and other menstrual symptoms, 56,57 it was worrying that coaches, as well, were hesitant to modify training sessions or allow athletes breaks from training in response to their menstrual symptoms. 30,39,40 While non-elite and recreational athletes were more likely to miss or adapt training sessions, 30,31,48 the tendency among elite athletes to continue training and competing, despite facing menstruation-relation pain and discomfort, 28,32 pointed to the potential health risks imposed by the performance-oriented and results-driven nature of elite sporting environments.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PA was corrected for hormonal contraceptive use in this study, and women with endometriosis still had lower PA. Hormonal contraceptives are frequently prescribed to manage symptoms of endometriosis, such as pain and heavy menstrual bleeding. However, studies have suggested that hormonal contraceptives can affect energy levels and motivation for PA, and further investigation is warranted to understand the impact of hormonal contraceptives on PA levels in women with endometriosis [28][29][30].…”
Section: Discussionmentioning
confidence: 99%